Climate resilience of makhana cultivation in flood-prone and waterlogged region - KRISHNA, BAL; Sundaram, Prity; Mahto, Dilip Kumar; Kumar, Rakesh (Indian Horticulture, 2026)
Makhana (Euryale ferox), a highly valued aquatic crop, has emerged as a climate-resilient farming option in flood-prone and waterlogged regions of India, particularly in Bihar, West Bengal, and parts of eastern Uttar Pradesh. Its unique adaptability to stagnant and shallow aquatic ecosystems makes it an ideal crop for areas frequently affected by excessive rainfall, prolonged submergence, and soil saturation conditions that hinder conventional agricultural production systems. The climatic resilience of makhana cultivation is attributed to its tolerance to waterlogging, efficient nutrient recycling, and compatibility with integratedfarming systems such as fish–makhana–vegetable models. With minimal external input requirements and the ability to restore soil fertility through organic biomass accumulation, makhana offers a sustainable livelihood alternative for marginal farmers in vulnerable ecosystems. Enhancing agro-techniques, strengthening policy support, and improving socio-economic linkages can further expandmakhana cultivation as a nature-based solution to climate risks.